2011
DOI: 10.1158/1541-7786.mcr-10-0515
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Epigenetic Silencing Associates with Deregulation of Ikaros Targets in Colorectal Cancer Cells

Abstract: Transcription factors are common targets of epigenetic inactivation in human cancer. Promoter hypermethylation and subsequent silencing of transcription factors can lead to further deregulation of their targets. In this study, we explored the potential epigenetic deregulation in cancer of Ikaros family genes, which code for essential transcription factors in cell differentiation and exhibit genetic defects in hematologic neoplasias. Unexpectedly, our analysis revealed that Ikaros undergoes very specific promot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 26 publications
1
46
0
Order By: Relevance
“…The identification of IKZF1 was particularly unusual, as it is a well-established T cell differentiation factor, though it is not without precedent that IKZF1 may have a role in cells outside the immune system (Javierre et al, 2011). However, it is important to note that this analysis does not imply that a master regulator such as IKZF1 has no role in T cells contributing to AA pathogenesis, but rather, that there is significant evidence that IKZF1 additionally functions in the scalp skin to mediate the interactions between the tissues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of IKZF1 was particularly unusual, as it is a well-established T cell differentiation factor, though it is not without precedent that IKZF1 may have a role in cells outside the immune system (Javierre et al, 2011). However, it is important to note that this analysis does not imply that a master regulator such as IKZF1 has no role in T cells contributing to AA pathogenesis, but rather, that there is significant evidence that IKZF1 additionally functions in the scalp skin to mediate the interactions between the tissues.…”
Section: Resultsmentioning
confidence: 99%
“…The losses of IKZF1 and DLX4 loci are also associated with oncogenesis in colorectal, lung, and breast cancers, and low-grade squamous intraepithelial lesions (Javierre et al, 2011; Sakane et al, 2015; Tomida et al, 2007). These studies obtain their genomic information directly from tumor masses, indicating that somatic losses of these two loci can contribute to cancer pathophysiology as end organ genomic alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Since regional gene silencing and DNA methylation or Long Range Epigenetic Silencing (LRES), defined as regions in the range from <1 Mbp to ~4 Mbp, has been observed in CRC [41] and other cancers [42,43] and one of our lead candidate genes, IKZF1 had been reported to be in an LRES region [33], we considered the location of genes we identified as methylated in CRC. Among the combined list of 74 Bisulfite-Tag and SuBLiME genes/regions, 23 genes were found within 3 Mb of at least one of the other genes - 8 pairs and one cluster each of 3 or 4 genes (Additional file 2: Table S11).…”
Section: Discussionmentioning
confidence: 99%
“…Hamada et.al found that miR-197 overexpression directly down-regulated p120 catenin, as a tumor suppressor, which bound to E-cadherin promoter repressed its stability and trafficking then induced EMT (Hamada et al, 2013;Stairs et al, 2011). Furthermore, several tumor suppressor genes such as CTNNAI, IKZFI, or EBF3 (Bennett et al, 2008;Ye et al, 2009;Javierre et al, 2011), might become novel targets of miR-197 during EMT induction, of which much work is warranted. Recently, in a retrospective study, J. Remon et al suggested that high-miR-197 might predict the risk of brain metastases information in EGFR-mutant-NSCLC (Remon et al, 2015) and EGFR mutational status represented a better overall survival in NSCLC with brain metastasis (Eichler et al, 2010).…”
Section: Mir-197 In Invasion and Metastasismentioning
confidence: 99%
“…Overall, it discovered that miR-197 contributed to the oncogenic activation of STAT3 via multiple targets through the upregulation of CKS1B. Apurinic/ apyrimidinic endonuclease 1 (APE1) had an important function in DNA repair and redox regulation, which had an influence on the sensitivity of tumor cells to chemotherapy (Tell et al, 2010) and took part in many signaling pathways, like p53, TGF-β (Sakai et al, 2015), WNT/ β-catenin, NRF1 (Javierre et al, 2011;Li and Wilson, 2014;Kan and Dong, 2015;Jiang et al, 2015;Garcia-Diaz et al, 2015). A study reported that miR-197 had a putative relationship with APE1, so we can pay high attention to miR-197/APE1 with other factors, which will be a meaningful pathway to tumorigenesis and chemoresistance.…”
Section: Mir-197 In Drug Resistancementioning
confidence: 99%